Relevance of LIS Professional Networking: Study and Analysis of Orcut Social Group - Krishna, K. M. (Journal of Information and Knowledge, 2011)
Attempt has been made in this article to study and analyse the importance of Social Networking, especially for the benefit of Library and Information Science Professionals. Orcut has been taken for the Case Study.